AIIALISIS TEORI DAN EKSPERIMENTAL PENGUMPUL SURYA DUA-PASS DENGAN MEDIA BERPORI - Supranto Supranto (Eksergi, 2010)
The double-pass solar collector with porous media in the lower channel provides a higher outlet temperature compared to conventional single-pass collector. Therefore, the thermal efficiency of the solar collcctor is higher. The solar collector can be used for wide variety of applications such as solar industrial process heat and solar drying of agricultural products. A theorelical model has been developed the double-pøss solar collector. Anexperimental setup has been designed and constructed. Comparison of the theoretical and the experimental results have been conducfecl such comparisons include the outlets temperatures and thermal eficiencies of the solør collector for various design and operating conclitions. Close agreement has been obtained between the theoretical and experimental results.